Commodity prices and growth: An empirical investigation. - Collier, P; Goderis, B (Elsevier, 2012)
Whereas empirical evidence on the effect of higher commodity prices on the long-run growth of commodity exporters is ambiguous, time series analyses using vector autoregressive (VAR) models have found that commodity booms raise income in the short run. In this paper we adopt panel error correction methodology to analyze global data for 1963 to 2008 to disentangle the short and long run effects of international commodity prices on output per capita. Our results show that commodity booms have unconditional positive short-term effects on output, but non-agricultural booms in countries with poor governance have adverse long-term effects which dominate the short-run gains. Our findings have important implications for non-agricultural commodity exporters with poor governance, especially in light of the recent wave of resource discoveries in low-income countries.